Restorative Justice: an Alternative Process for Solving Juvenile Crimes in Indonesia - Jufri, Mahfud; Nazeri, Norbani Mohamed; Dhanapal, Saroja (Faculty of Law, Universitas Brawijaya, 2019)
Restorative justice concept may refer to an alternative process for solving disputes including criminal law violation has been well known in Indonesia. The Act Number 11, 2012 on Juvenile Justice System has acknowledged restorative justice approach as a part of criminal justice system in dealing with a child in conflict with the law. It has become an essential provision in the Act as it provides option for law enforcers to avoid punishing juvenile offenders through traditional criminal approach. This research aims to examine restorative justice for juvenile offenders in Indonesia based on the Juvenile Justice System Act Number 11, 2012 as a form of alternative dispute resolution for juvenile crimes and other related laws and to provide a brief of the implementation of restorative justice in Indonesia that is integrally enforced in Indonesian criminal justice system dealing with a child in conflict with the law. It divides the discussion into two parts restorative justice in the juvenile justice system act 2012 and the implementation of restorative juvenile justice in Indonesia. In order to response to these research aims, this paper employs doctrinal legal research.